Cognitive And Lingua-Cultural Aspects Of The Concept Of The Numerals In Kazakhstan - Kalbike O. Yessenova, Zhuldyz B. Kurmambayeva, Zhanalyk K. Baltabayeva,; Botagoz S.Ashirova, Tanat T. Ayapova, (Opción, 2019)
This article deals with the study of language and culture and with the notion of the concept via cognitive and lingua-cultural approaches. With the help of these approaches we could find valuable information about mentality of the people with their life, history and culture. As a result, the numerals with national codes tell readers about, the way their ancestors lived, the culture and traditions which pass from one generation into other generations. In conclusion, Lingua-cultural study of Kazakh numerals with national codes lets young generation respect the people and feel proud of their history, tradition and culture.